A kinetic model for isotopologue signatures of methane generated by biotic and abiotic CO2 methanation. (15th March 2019) - Cao, Xiaobin; Bao, Huiming; Peng, Yongbo
Abstract: Methane has both biotic and abiotic origins, and the identification of its origins has important implications in understanding terrestrial processes as well as in searching for extraterrestrial life. Bulk stable isotope ratios ( 13 C/ 12 C and D/H) and multiply substituted isotopologues ( 13 CH3 D and 12 CH2 D2 ) have been used to distinguish methane's origins, and kinetic models are essential to understanding and quantifying these isotopologue signatures. Although different kinetic models have been developed, inconsistencies exist within these models. Here we constructed an isotopologue-specific kinetic model to quantify isotopologue signatures of methane generated by biological- and metal-catalyzed CO2 methanation. The Monte Carlo method and data from two experiments were used to constrain the kinetic reversibility and associated isotope effects. The results show that the reversibility can be the same for the biotic and abiotic CO2 methanation pathways, and their distinct isotopic signatures depend on their respective hydrogen sources. Biotic methane sources hydrogen from carbon-hydrogen and sulfur-hydrogen bonds while abiotic methane sources from metal-hydrogen adsorption bonds. This hydrogen source difference results in abiotic methane being more depleted in 12 CH2 D2 relative to biotic methane. Although kinetic and dynamic complexities may prevent differentiation between biotic and abiotic methane in multiple and clumped isotope spaces, our proposed molecular-level difference in hydrogen source provides a universal basis for analyzing the isotopologue signatures of methane of diverse origins.